Spectrum of non-motor neuropsychiatric symptoms among patients with Parkinson’s disease and Parkinson plus syndrome - VK Verma; Anoop Kumar; RR Singh; D Uraiya; N. Tripathi (International Journal of Medical Research and Review, 2016)
Introduction: Patients with PD often have non motor symptoms in addition to the motor manifestations of bradykinesia, rigidity and tremor. The NMSs are more often seen in patients with longer duration of disease. There is increasing realization that NMSs significantly contribute to the morbidity and increase the burden of the disease far beyond that caused by the classical motor symptoms.Material and methods: It was a cross sectional study conducted to assess the non-motor dysfunction in 60 patients with Parkinsonism including idiopathic Parkinson’s disease and Parkinson plus syndrome who attended either the outdoor services, or were admitted in the Neurology ward of our tertiary care centre, PGIMER & Dr. RML Hospital, New Delhi, India.Results: Out of 40 patients with Parkinson’s disease, twenty-five (62.50%) were males and 15 (37.50%) were females with mean age of 55.02 (SD ±13.56) years. Among patients with MSA, six (66.70%) were male and 3 (33.33%) were female with mean age of 62.00 (SD ±11.38) years. Out of 40 patients with PD 19 (47.50%) had minimal depression, 12 (30%) mild depression, 7 (17.50%) moderate depression and 2 (5%) severe depression. Out of 20 patients with Parkinson plus Syndrome 12 (60%), 5 (25%), and 3 (15%) patients had minimal, mild and moderate depression.Conclusion: Parkinson’s disease and Parkinson plus syndrome are group of sporadic, neurodegenerative diseases of the central nervous system. There are only a few reports about the frequency of neuropsychiatric symptoms in patients with Parkinson disease from India and no such Indian report in patients with Parkinson plus syndrome